Kontribusi Etika Islam terhadap Teori Penawaran: Kajian Liter-atur Kualitatif - Saputra, Rio Panji; Winario, Mohd (EL-EMIR Institute, 2025)
Supply theory in conventional economics generally emphasizes the rationality of producers in making economic decisions with the primary goal of maximizing profits. This approach views producers as economic actors acting based on cost-benefit considerations, but often ignores the ethical and moral dimensions of the production, distribution, and pricing of goods and services. As a result, economic practices detrimental to society, such as hoarding, price manipulation, and resource exploitation, often occur. Islam, as a comprehensive value system, offers a set of ethical principles that can enrich and complement modern supply theory. This article aims to examine the contribution of Islamic ethics to supply theory through a qualitative literature review approach. Data were obtained from various scientific sources, including journals, books, and relevant academic publications from the past five years. The results of the study indicate that Islamic ethics makes a significant contribution to supply theory through its emphasis on honesty, justice, social responsibility, and the prohibition of economic practices that harm society. The integration of Islamic ethics into supply theory has the potential to create a more just, sustainable, and oriented economic system that benefits the community as a whole.